Agreement Between Isokinetic Dynamometer and Hand-held Isometric Dynamometer as Measures to Detect Lower Limb Asymmetry in Muscle Torque After Anterior Cruciate Ligament Reconstruction - Angelica Ivarsson; Anna Cronström (International Journal of Sports Physical Therapy)
# Background